2017
DOI: 10.1007/s10554-017-1139-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving risk assessment for post-surgical low cardiac output syndrome in patients without severely reduced ejection fraction undergoing open aortic valve replacement. The role of global longitudinal strain and right ventricular free wall strain

Abstract: Low cardiac output syndrome (LCOS) after surgical aortic valve replacement (SAVR) is related to increased mortality and treatment related costs. We aimed to evaluate whether echocardiography-derived left ventricular global longitudinal strain (LV-GLS) relates to the occurrence of postoperative LCOS in patients undergoing SAVR. We prospectively enrolled 75 patients with symptomatic severe aortic stenosis, left ventricular ejection fraction (LVEF) >40%, NYHA Class Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
(23 reference statements)
2
11
1
2
Order By: Relevance
“…The effect of age on the risk of LCOS in adults has been confirmed earlier. In a prospective study, multivariate analysis showed that age was an independent predictor of LCOS [9] and a retrospective study ascertained that increasing age is an independent predictor of LCOS [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of age on the risk of LCOS in adults has been confirmed earlier. In a prospective study, multivariate analysis showed that age was an independent predictor of LCOS [9] and a retrospective study ascertained that increasing age is an independent predictor of LCOS [2].…”
Section: Discussionmentioning
confidence: 99%
“…Prediction models based on clinical data, such as EuroSCORE, have been proposed [8]. However, the risk factors of LCOS are varied in the literature according to the population and surgery categories included [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Both systolic and diastolic function has been found to impact the outcome of an aortic valve intervention 79,80 . Previous studies have identified both pre-and intraoperative risk factors for PHF [81][82][83] . Studies on patients that have undergone non-cardiac surgery have shown that the best therapeutic approach to heart failure in the surgical setting is to perform proper patient risk stratification 84 .…”
Section: Myocardial Dysfunction In Aortic Valve Surgerymentioning
confidence: 99%
“…Pre-and postoperative characteristics. 70 [65][66][67][68][69][70][71][72][73][74][75][76] 75 [68][69][70][71][72][73][74][75][76][77][78][79] 0.08 60 <0.001 82 [76][77][78][79][80][81][82][83][84][85] Values are given as n (%) and median (25 th to 75 th percentile).…”
Section: Study IIImentioning
confidence: 99%
“…Low cardiac output syndrome (LCOS) is the most serious complication, which associated with increased morbidity, and treatment-related costs [5]. Recent studies suggest a wide LCOS incidence of 3.9-41% [3,6,7]after heart valve surgery. For these patients, LCOS is associated with a 30-day mortality rate of 12.8-38% [3,6,8].…”
Section: Introductionmentioning
confidence: 99%